An abnormal hermaphroditic skipjack, Katsuwonus pelamis (Linnaeus, 1758) from Agatti coast, Lakshadweep, India - Pillai, N G K; Jabbar, B; Mallia, J V; Muhsin, A I (Indian Journal of Fisheries, 2011)
A hermaphroditic specimen of skipjack tuna, Katsuwonus pelamis of forklength (FL) – 56 cm and total weight (TW) – 3.20 kg was caught by pole and line on 21st November 2005 from the Agatti coast, Lakshadweep. Histological studies revealed that both the ovarian and testicular portions had developed a completeseries of gametogenic cell lines.